2020
DOI: 10.1163/15707563-bja10005
|View full text |Cite
|
Sign up to set email alerts
|

Variation in reproductive output as a function of maternal age and weather conditions in the cultured Asian yellow pond turtle, Mauremys mutica

Abstract: Biotic factors (e.g., maternal age) and abiotic factors (e.g., weather) play vital roles in reproduction. However, there is little information about the combined effects of maternal age and weather on the reproductive output of cultured Asian yellow pond turtles, Mauremys mutica. To address this issue, we surveyed and compared the reproductive output of 13-year-old and 25-year-old female turtles on non-rainy and rainy days. The results showed that older females produced larger eggs than younger females regardl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Here, the mean body mass of newly hatched offspring every year increased over the four years, and there were significant differences found in the offspring body mass within the females across the years, except for 2014 and 2015. Given that the body masses of the neonates were not related to maternal size, we speculated that the offspring’s body mass might be strongly associated with maternal age [ 41 ], which is also verified in another research study of M. mutica [ 42 ]. It was reported that the age effect might have something to do with the “overhead” costs, which were ignored in previous studies and theory, in influencing reproduction and sexual maturation [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 77%
“…Here, the mean body mass of newly hatched offspring every year increased over the four years, and there were significant differences found in the offspring body mass within the females across the years, except for 2014 and 2015. Given that the body masses of the neonates were not related to maternal size, we speculated that the offspring’s body mass might be strongly associated with maternal age [ 41 ], which is also verified in another research study of M. mutica [ 42 ]. It was reported that the age effect might have something to do with the “overhead” costs, which were ignored in previous studies and theory, in influencing reproduction and sexual maturation [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 77%